In-house Multiplex rRT-PCR Assay for Sars-Cov2 Detection in Indonesia using a new primer design - Gaffar, Shabarni; Putri, Rafika Nanda; Shabrinna, Hanif; Supriyadi, Isma Yustifania; Wiraswati, Hesti Lina; Ekawardani, Savira; Ishmayana, Safri; Hartati, Yeni Wahyuni; Faridah, Lia (Universitas Andalas, 2025)
During the COVID-19 pandemic, we attempted to develop an in-house rRT-PCR kit, utilizing custom primers targeting NSP14 and RdRp, with the RPP30 gene as an internal control. This kit will support Indonesian independence in enhancing COVID-19 diagnostics. The primer and probe were designed by a bioinformatics tool, determining primer specificity and sensitivity, optimizing probe concentrations, establishing LoD (Limit of Detection), LoQ (Limit of Quantification), and rRT-PCR efficiency, multiplex testing of the rRT-PCR kit on clinical samples, and testing the kit's stability. The in-house rRT-PCR kit can detect NSP14, RdRp, and RPP30 genes. The optimal concentrations for the NSP14, RdRp, and RPP30 probes are 1 μM, 1.5 μM, and 1.5 μM, respectively. The LoD and LoQ for the NSP14 are 0.22 ng/μL and 0.67 ng/μL, and for the RdRp are 1.08 ng/μL and 3.28 ng/μL. The rRT-PCR efficiencies for the NSP14, RdRp, and RPP30 are 80.3%, 100.6%, and 106%, respectively. Detection of ten clinical samples, comprising seven true positive and three true negative samples, showed Ct (Cycle threshold) values of 28–31 for the RPP30 gene, Ct 21–27 for the RdRp gene, and Ct 30–34 for the NSP14 gene. Stability testing of the rRT-PCR kit demonstrated promising results, where the kit stored at -20°C for seven days showed almost no difference in Ct values. This in-house multiplex rRT-PCR will support Indonesian independence in enhancing COVID-19 diagnostics, providing a dependable method for detecting SARS-CoV-2 in clinical samples.